Implementasi Konsep Timor Pada Perancangan Interior Restoran Timor Di Kota Kupang - Nusa Tenggara Timur - Fiorentin Callista Shianto; Ronald Hasudungan Irianto Sitindjak; Linggajaya Suryanata (Intra, 2017)
Local culture as a concept of interior design design is often considered outdated for modern society. In fact, local culture in Indonesia has variety of values and arts. One of the least exposed is the Timor culture originating from Kupang, East Nusa Tenggara. The culture of Timor can be applied to the interior design of the restaurant as one of the business areas with a high number of enthusiasts. This design offers the concept for visitors to enjoy entertainment and socialize while enjoying the food and drinks provided. The restaurant provides food and beverage service that offers an ethnic and artistic atmosphere. With this design, people's point of view of local culture will get better.